Anthropological challenges of transhumanism - Arana, Juan (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In the literature on transhumanism there is a lot of space devoted to descriptions and taxonomies, but little in-depth discussion of the bases and limits of the underlying theoretical approaches. Critics gamble too much on ad hominem arguments, while supporters linger more than they should in extolling the future benefits of exponentially accelerated progress. In this text an attempt is made to carry out a more serene reflection, centered on the notions of «human essence», «naturalization» and «self-consciousness».